Economic Security And The Forecasting Of Employee Dismissals As A Building Block For Creating A Personnel Strategy - Bartosz KOZICKI; Szymon MITKOW; Jarosław TOMASZEWSKI; Paweł JAŚKIEWICZ (Communications of International Proceedings, 2021)
The article presents the issue of economic security and the forecasting of dismissals for 2018-2019 based on primary information obtained from the research subject. The research began with an analysis and evaluation of the time series related to admissions to work between 2011-2017. Then, the original time series of dismissals was divided into teaching and testing parts. Using the obtained evaluation, the forecasting was conducted on the basis of the training series with the application two forecasting methods which were analyzed and evaluated on the basis of the testing series. The results of the evaluation made it possible to choose the best method for the forecast of the primary series. The forecast of dismissals for 2018 amounted to 3306 employees while in 2019 it decreased to 3032 people.
Keywords: economic security; personnel strategy; forecasting; data analysis.